2008
DOI: 10.1007/s10509-008-9756-0
|View full text |Cite
|
Sign up to set email alerts
|

On nova Scorpii 2007 N.1 (V1280 Sco)

Abstract: We present the results of our photometric and spectroscopic observations of Nova Sco 2007 N.1 (V1280 Sco). The photometric data was represented by a single data point in the light curve since the observation was carried out only for one night. The spectra cover two different phases of the object's evolution during the outburst, i.e. pre-maximum and post-maximum. Measurements of the P-Cygni profile on Na I 'D' line (5889 Å) was derived as the velocity of shell expansion, yielding 1567.43 ± 174.14 km s −1 . We c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
(6 reference statements)
0
4
1
Order By: Relevance
“…Large post maximum oscillations have been previously observed in the novae V2540 Oph (Kato et al 2002), V1178 Sco (Kato and Mitsugu 2001), V4361 Sgr (Kato and Mitsugu 2001), V2214 Oph (Lynch et al 1989), V868 Cen (Williams et al 2003). This behavior is markedly different from the dips and returning to decline curve shown by dust forming novae, such as V1280 Sco (Kuncarayakti et al 2008).…”
Section: Photometrycontrasting
confidence: 62%
“…Large post maximum oscillations have been previously observed in the novae V2540 Oph (Kato et al 2002), V1178 Sco (Kato and Mitsugu 2001), V4361 Sgr (Kato and Mitsugu 2001), V2214 Oph (Lynch et al 1989), V868 Cen (Williams et al 2003). This behavior is markedly different from the dips and returning to decline curve shown by dust forming novae, such as V1280 Sco (Kuncarayakti et al 2008).…”
Section: Photometrycontrasting
confidence: 62%
“…There are very few novae for which the spectral evolution before the maximum brightness has been documented, e.g. V1280 Sco (Kuncarayakti, Kristyowati & Kunjaya ; Naito et al ) and V2615 Oph (Munari et al ). The spectral evolution of V496 Sct during the pre‐maximum, maximum and optically thick branch of the decline phase is presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The optical spectra presented here cover the pre-maximum rise, the optical maximum brightness, the early decline and the nebular phase. There are very few novae for which the spectral evolution before the maximum brightness has been documented: V1280 Sco (Naito et al 2012, Kuncarayakti et al 2008) and V2615 Oph (Munari et al 2008). The spectral evolution of V496 Sct during the pre-maximum, maximum and optically thick branch of the decline phase is presented in Fig.…”
Section: Line Identification Evolution and General Characteristics Of...mentioning
confidence: 99%
“…Its early spectra were taken by some observers (e.g. Naito & Narusawa 2007, Kuncarayakti et al 2008) and it was classified as an Fe ii type nova ). Yamaoka et al (2007c) reported that the spectrum at the pre-maximum stage looked like that of an F-type supergiant dominated by absorption lines of hydrogen, Fe ii and other metals.…”
Section: Introductionmentioning
confidence: 99%